The Origins of Import Substituting Industrialization in India. Issue 1 (2nd January 2017) - Roy, Tirthankar
ABSTRACT: In the post-war world, India was one of the most protectionist countries. Protectionism originated in British colonial measures to design an industrialization policy in the 1920s. Whereas in the 1920s, protection was applied with discrimination, after independence in 1947, protection was offered without discrimination. The paper explains how this transformation came into being. It rejects the hypothesis now current that discriminating protection was dropped because it was a weak policy, and suggests instead that the aspirations of nationalistic businesses played a role.